1999
DOI: 10.1046/j.1464-5491.1999.00007.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and management of hypertension in Type 1 diabetes mellitus in Europe: the EURODIAB IDDM Complications Study

Abstract: These data show the extent of undermanagement of hypertension in Type 1 DM across Europe prior to the publication of the St. Vincent Declaration and provide a useful baseline against which future improvements in the management of hypertension can be monitored.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
29
1
5

Year Published

1999
1999
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(40 citation statements)
references
References 28 publications
5
29
1
5
Order By: Relevance
“…Thus, the proportion of patients considered to be hypertensive in our study was relatively high. This situation is probably caused by antihypertensive treatment for albuminuria in normotensive patients (especially ACE inhibitors), an issue also previously addressed by others (32,34). Successful blood pressure control with blood pressure Ͻ130/80 mmHg in both 1997 and 2004 was predicted by young age, female sex, short diabetes duration, low BMI in 1997, weight loss during the period, and absence of microalbuminuria in 1997.…”
Section: Conclusion -In This Surveymentioning
confidence: 84%
“…Thus, the proportion of patients considered to be hypertensive in our study was relatively high. This situation is probably caused by antihypertensive treatment for albuminuria in normotensive patients (especially ACE inhibitors), an issue also previously addressed by others (32,34). Successful blood pressure control with blood pressure Ͻ130/80 mmHg in both 1997 and 2004 was predicted by young age, female sex, short diabetes duration, low BMI in 1997, weight loss during the period, and absence of microalbuminuria in 1997.…”
Section: Conclusion -In This Surveymentioning
confidence: 84%
“…In 3,250 type 1 diabetic subjects seen in 1989 -1990 with a mean age of 32.7 years and duration of diabetes of 14.7 years, 24% had hypertension, of whom 48.5% were aware of the diagnosis and 42.2% were on treatment with only 11.3% controlled. Additionally, 81% of those on treatment were on only one antihypertensive medication (17). In the EURODIAB 7-year follow-up data, hypertension prevalence had increased from 412 to 631 subjects out of 1,866 subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Reports on prevalence, awareness, treatment, and control of hypertension exist for the general population (10,11) and the type 2 diabetic population (12)(13)(14)(15)(16), whereas data for patients with type 1 diabetes are limited, consisting of two EU-RODIAB reports (17,18) and one abstract from Pittsburgh (19). In the published reports on hypertension in type 1 diabetes, control groups are not included.…”
mentioning
confidence: 99%
“…203 Another small study of T1DM showed 29% of patients had hypertension; the hypertension correlated with disease duration and severity, particularly nephropathy, 204 similar to findings from the EURODIAB Study. 205 A recent analysis of the predictors of major T1DM outcomes in the Pittsburgh EDC study showed that although glycemic control diminished in importance over time, hypertension continued to be a strong CVD predictor. 206 This may reflect the better glycemic control experienced by the later cohort, and perhaps the lack of amelioration of the profound adverse effects of hypertension on DM outcomes.…”
Section: Hypertensionmentioning
confidence: 99%